2004
DOI: 10.1017/s0030605304000341
|View full text |Cite
|
Sign up to set email alerts
|

The decline of the Chinese giant salamander Andrias davidianus and implications for its conservation

Abstract: The Chinese giant salamander Andrias davidianus is the largest living amphibian. Most wild populations are threatened and some are already extinct. The Chinese government has declared the species a Class II Protected Species, and it is listed as Critically Endangered in the Chinese Red Book of Amphibians and Reptiles and as Data Deficient on the IUCN Red List. Populations of the species have declined sharply in both range and number since the 1950s because of habitat loss and fragmentation, and hunting for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 1 publication
2
64
0
Order By: Relevance
“…An AMOVA further revealed that among-group comparisons were responsible for <1% of the genetic variation, supporting the notion that modern-day populations are not strongly structured with respect to river systems. Chinese giant salamanders are kept in captivity in China for both conservation and exploitative purposes (Wang et al 2004). Recently several captive salamander colonies have experienced significant die offs due to disease (Dong et al 2010).…”
Section: Amphibian Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…An AMOVA further revealed that among-group comparisons were responsible for <1% of the genetic variation, supporting the notion that modern-day populations are not strongly structured with respect to river systems. Chinese giant salamanders are kept in captivity in China for both conservation and exploitative purposes (Wang et al 2004). Recently several captive salamander colonies have experienced significant die offs due to disease (Dong et al 2010).…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…Like all members of the family Cryptobranchidae, Andrias are obligatorily aquatic and are restricted to large, permanent riverine habitats. The species faces a host of threats, ranging from habitat loss and poaching (Wang et al 2004) to disease (Geng et al 2011). Wang et al (2004 evaluated A. davidianus habitat, conducted population surveys and polled wildlife managers and villagers in 13 sites throughout five different provinces and the city of Chongqing.…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…There are more than two hundred salamander taxa identified in the United States, and at least 29% are ranked by NatureServe as "imperiled or critically imperiled" in a portion of their ranges (roughly equivalent to the IUCN's Red List designation of "critically endangered," "endangered," and "vulnerable") [33]. Potential and established reasons for their decline include forest fragmentation and habitat alteration [41], land use disturbance and urbanization [42,43], epidemic disease [44,45], climate change [44,46], pollutants/contaminants [44,45], acidic deposition [47,48], harvest/predation [45,49], and interactions between these factors [50]. To direct conservation and management efforts in the United States and worldwide, it is important to understand, as thoroughly and holistically as possible, the roles of environmental parameters and the impacts of human activities on salamander abundance and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The population of Chinese giant salamanders has decreased sharply due to infectious disease, habitat loss, environmental pollution and overharvesting (Wang et al 2004). In the past few years, both juvenile and adult life stages of this animal have been impacted by various diseases.…”
Section: Introductionmentioning
confidence: 99%